The Relationship between Planar and SPECT/CT Parameters and Functional Markers in Primary Hyperparathyroidism - Guler Silov; Serpil Erdogan Ozbodur (Diagnostics, 2023)
This study aimed to investigate the relationship between quantitative and volumetric parameters of technetium-99-methoxyisobutylisonitrile (99mTc-MIBI) single-photon emission computed tomography/computed tomography (SPECT/CT) imaging and hormonal and biochemical markers in primary hyperparathyroidism (PHPT) patients with single adenoma. In this retrospective study, 70 patients with a single adenoma who underwent 99mTc-MIBI imaging for the diagnosis of PHPT were examined. Early and delayed MIBI lesion/background ratios (eLBR and dLBR), early and delayed lesion/thyroid ratio (eLTR and dLTR), and retention index (RI) were calculated as planar dual-phase scintigraphy parameters. Adenoma volume (Svol) and parathormone (PTH)/Svol ratio were measured as SPECT/CT-derived parameters. Calcium levels exhibited a positive correlation with eLBR (r = 0.33, p < 0.001), dLBR (r = 0.29, p = 0.01), dLTR (r = 0.31, p < 0.001), and PTH/Svol (r = 0.38, p < 0.001). PTH did not correlate with planar parameters and Svol. Among the imaging parameters, only the PTH/Svol ratio showed a negative correlation with phosphorus levels (r = −0.29, p = 0.02). For predicting disease severity, the PTH/Svol ratio exhibited similar diagnostic performance to PTH and phosphorus levels but outperformed the eLBR and dLBR. Both planar and SPECT-derived parameters can provide valuable insights into the functional status of the parathyroid adenoma and the associated disease severity. PTH/Svol ratio, combining imaging and laboratory findings to provide a more comprehensive approach to patient care, could be an exciting new indicator.